Model Akuntabilitas dalam Pengelolaan Barang Bukti untuk Peningkatan Pelayanan Publik di Kejaksaan Negeri Palembang - Wawan Setiawan; Andries Lionardo; Slamet Widodo; Alfitri Alfitri (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2026)
Accountability is a fundamental principle in the provision of public services, including in the law enforcement sector. The management of evidence is not merely a technical-administrative function, but has direct implications for legal certainty, procedural justice, and public trust. This study aims to analyze the dynamics of accountability in evidence management at the Palembang District Attorney’s Office, identify its supporting and inhibiting factors, and formulate an accountability model to improve the quality of public services. The study employs a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and document analysis, and analyzed interactively using the framework of public accountability theory, the New Public Service paradigm, and principles of good governance. The findings indicate that accountability in evidence management has been implemented formally and administratively, but has not yet fully manifested as substantive accountability oriented toward public service. Accountability practices remain dominated by internal responsibility and procedural compliance, while transparency and access to information for litigants are still limited. This study proposes a public service–based accountability model for evidence management that is adaptive and collaborative in order to strengthen service quality and institutional legitimacy of the prosecution service.